The Implications of DNA Methylation on Food Allergy - Lee, K.; Song, Y.; O'Sullivan, M.; Pereira, Gavin; Loh, R.; Zhang, G. (2017)
Food allergy is a major clinical and public health concern worldwide. The risk factors are well defined, however, the mechanisms by which they affect immune development remain largely unknown, and unfortunately the effective treatment or prevention of food allergy is still being researched. Recent studies show that the genes that are critical for the development of food allergy are regulated through DNA methylation. Environmental factors can affect host DNA methylation status and subsequently predispose people to food allergy. DNA methylation is therefore an important mediator of gene-environment interactions in food allergy and key to understanding the mechanisms underlying the allergic development. Indeed, the modification and identification of the methylation levels of specific genetic loci have gained increasing attention for therapeutic and diagnostic application in combating food allergy. In this review, we summarize and discuss the recent developments of DNA methylation in food allergy, including the pathogenesis, therapy, and diagnosis. This review will also summarize and discuss the environmental factors that affect DNA methylation levels in food allergy.